Experimental and Analytical Investigation of Point Fixed Corrugated Metal Sheets Subjected to Blast Loading - FISCHER, Kai; STOLZ, Alexander; ROLLER, Christoph (Engineering Transactions, 2019)
Besides the primary threats of a blast loading scenario, flying fragments from nonstructural elements could be a further threat to exposed humans. Point fixed corrugated metal sheets are often applied as facade elements. This paper focuses on the analysis of the dynamic bearing resistance and related pull-out behaviour of such elements. In a first step, the dynamic bearing capacity is investigated by an experimental study. Different sheet thicknesses and dimensions are examined for different loading levels using shock tube experiments. Based on the experimental results an engineering model is applied to predict the overall bearing capacity of the investigated corrugated metal sheet elements using mathematical optimisation methods. In a second step, the comparison to an analytical approach to quantify the prognostic capacity of the theoretical assessment method is addressed. Obtained results enable fast and effective quantification of expected damage effects and can be integrated into an overall risk and resilience analysis scheme.